The synthesis and optical dispersions parameters of Cadmium doped Tin-oxide thin films by the Sol-Gel method - Aydın, Cihat; Aydın, Handan (Niyazi BULUT, 2021)
In this study, undoped and Cd-doped SnO thin movies with unique atomic contents (0, 2, 4, and six%) have been synthesized by means of the sol-gel method. The modifications in the optoelectrical residences of the Cd doped samples had been investigated with the aid of UV-VIS-NIR spectroscopy. The impact of Cd doping at the optical homes of the SnO films becomes investigated by means of spectrophotometric measurements. The optical constants (refractive index, n, and absorption index, okay) of the samples have been determined in the wavelength variety of 300-800 nm. The dispersion parameters have been determined consistent with the version of a single oscillator and discussed. The optical band gaps of the samples were calculated using Tauc equation. It became discovered that the Eg values of the samples increased from 3.57 eV to three.60 eV as a function of Cd doping. due to the studies, it turned determined that Cd doping has considerable results on the optical residences of SnO movies and the fabricated samples may be used for transparent conductive electrodes, optoelectronic gadgets, and sensor fabrication.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri